γ-rays irradiation eﬀects on dielectric properties of Ti/Au/GaAsN Schottky diodes with 1.2%N - Henini, M. (Elsevier, 2018)
Dielectric properties of As grown and irradiated Ti /Au/GaAsN Schottky diodes with 1.2%N are investigated using capacitance/conductance-voltage measurements in 90–290 K temperature range and 50–2000 kHz frequency range. Extracted parameters are interface state density, series resistance, dielectric constant, dielectric loss, tangent loss and ac conductivity. It is shown that exposure to γ-rays irradiation leads to reduction in effective trap density believed to result from radiation-induced traps annulations. An increase in series resistance is attributed to a net doping reduction. Dielectric constant (ε’) shows usual step-like transitions with corresponding relaxation peaks in dielectric loss. These peaks shift towards lower temperature as frequency decrease. Temperature dependant ac conductivity followed an Arrhenius relation with activation energy of 153 meV in the 200–290 K temperature range witch correspond to As vacancy. The results indicate that γ-rays irradiation improves the dielectric and electrical properties of the diode due to the defect annealing effect.